The Effectiveness of Learning Videos for Increasing Knowledge about Women's Adolescent Nutrition and Reproductive Health - Febriana, Rina; Devi Artanti, Guspri; Rusilanti, Rusilanti (KnE Social Sciences, 2020)
The purpose of this study was to obtain valid and reliable data or facts related to the effectiveness of instructional video media in improving nutritional knowledge and reproductive health in young women. The problem in this study is the lack of knowledge of young women about nutrition and reproductive health and the lack of use of learning media in schools. This research is quasi-experimental research in the form of a pretestposttest with a control group design with 180 respondents in several vocational schools in Jakarta and Bogor. The normality test is done using the formula Lilliefors and obtained Larithmetic for learning video media by 0.110 and Larithmetic for conventional media 0.126 with Ltable = 0.093, because Larithmetic > Ltable, it can be concluded that the two data is not normally distributed. The influence between the two groups can be seen using the Mann Whitney test to obtain a Zarithmetic of 1.539 and Ztable value at α = 0.05 of 1.200. Based on the calculation results, it can be concluded reject Ho if Zarithmetic > Ztable, which means H1 is accepted, and there is an increase in the knowledge of the experimental group given higher learning video media treatment compared to the control group given treatment using PowerPoint media. So it was concluded that there was an increase in knowledge on the use of video media for learning nutrition and reproductive health in young women. Keywords: video media, knowledge, young women, nutrition, reproductive health